ANEMIA PADA REMAJA PUTRI DI KECAMATAN CEMPAKA KOTA BANJARBARU - Yuniarti Yuniarti; Zakiah Zakiah (Sekolah Tinggi Pariwisata Mataram, 2021)
The teenage girls is a group to suffering from anemia. Anemia are public health problems, prevalensinya is still high especially in teenagers girls in the world of 30.2 percent, 45.7 percent in South Eastern Asia (WHO, 2008). City Banjarbaru including district with prevalence of anemia in teenagers higher than prevalence of South Kalimantan.The purpose of this research is to know factors that deals with anemia in teenage girls in Banjarbaru city 2018. The design of this study is descriptive analytic with cross sectional used a quantitative approach. The research variable is teenage knowledge, body image, drinking tea regulary, menstruation period, meal frequency, consumption supplements, mothers education, family size, family income, and anemia in teenage girls. This study conducted in Cempaka districts Banjarbaru city. The population in this study was teenage girls that studied in Junior High School Cempaka districts Banjarbaru city. Used clusters sampling with 115 respondents. Analysis bivariat used chi square and multivariate analysis with logistic regression test. There was a the relation between body image, consumption supplement with anemia in teenagers girls in banjarbaru city, there was no relation between knowledge, drinking tea regulary, menstrual period, meals frequency, mother education, family size and family income by anemia with anemia in teenagers girls in banjarbaru city